Does Coronavirus Pandemic Sentiment Drive FTSE 100 Index Return? Capturing and Measuring Coronavirus Sentiment Through the Utilisation of Google Trends - Eben, Jesslyn (2020)
COVID-19 or the coronavirus infectious disease has affected our lives greatly during this 2020. Even though it concerns medical attention, the impact of the mentioned pandemic draws concerns that affecting other sectors as well, especially on the economy. Quantifying the impact of the pandemic on the financial market has become great concerns for investors and policy makers, especially during its spreading period. In March 2020, the world experienced the most dramatic stock market plunge and even crashed for several days in response to the declaration of the disease as a pandemic. However, the dive was not instigated by poor corporate government, nor asset price bubble burst, and neither do the companies listed on the market has grown weaker. Looking into the phenomenon, it raises an empirical question whether it is possible that the dramatic fluctuation was due to investor sentiment.